Conservation and sustainable use of wildlife -based resources through the framework of the Convention on Biological Diversity (CBD): The Bushmeat Crisis - Christophersen, T.; Nasi, Robert (2008)
This articlepresents a number of policy recommendations to improve the sustainability of wildlife-based resources use in tropical forests, including by strengthening national ownership of this issue in a way that provides long-term local and national benefits. It also argues in favour of stronger involvement of civil society and the private sector in addressing governance issues and other aspects of current overexploitation of wildlife; enhancing local ownership rights; and establishing links between the bushmeat debate and tenurial and land-rights reform. At the international level, the authors suggest that trade relations between developed and developing countries, which (directly and indirectly) affect bushmeat consumption levels, must be seriously reconsidered, and that efforts should place a stronger emphasis on positive incentives for better managing wildlife resources.